Transformasi Budaya Islami melalui Pendidikan Agama Islam: Kajian Filosofis dan Pedagogis - Mutiara Ayu Pratiwi; Rahma Faudziah; Rahmad Nauli Nasution; Reva Fadhilah; Abdul Azis (Kampus Akademik Publiser, 2025)
Islamic Religious Education (PAI) has a strategic role in shaping the character, morals, and Islamic culture of learners amid the challenges of globalization and modernization that led to the decline of religious values and identity crisis. This condition requires the transformation of Islamic culture through education based on balanced spiritual and scientific values. This study aims to examine the role of PAI as a means of transformation of Islamic culture viewed from a philosophical and pedagogical perspective. The research method used is a qualitative approach with the type of literature study, which examines various relevant scientific literature to obtain a conceptual understanding of Islamic values, educational philosophy, and pedagogical strategies in the context of PAI learning. Data analysis was done with Miles and Huberman interactive model that includes reduction, presentation, and conclusion. The results show that the transformation of Islamic culture in PAI is rooted in a philosophical-theological foundation that emphasizes the balance between science, faith, and morality. Pedagogically, the transformation is realized through exemplary learning strategies, habituation, integration of Islamic values in the curriculum, and the use of contextual digital technology. The synergy between philosophical and pedagogical dimensions produces an Islamic educational paradigm that is integrative, adaptive, and relevant to the dynamics of modern society. PAI serves not only as a means of transferring religious knowledge, but also as an agent for the cultivation of moral and spiritual values in the lives of learners. Thus, the transformation of Islamic culture through PAI becomes an important step in building a generation of knowledge, faith, and noble character in the midst of rapid social change.